Current Research Describing the Role of CD4+ T Lymphocyte Subsets in the Pathogenesis of Granulomatous Lobular Mastitis. Issue 10 (3rd October 2022) - Zheng, Bilian; Song, Junlong; Lu, Man; Chen, Chuang; Sun, Shengrong
Abstract: Background: Granulomatous lobular mastitis (GLM) is a rare, benign, chronic inflammatory illness of the mammary gland with an unknown cause. Many scholars believe that the pathogenesis of GLM is mediated by autoimmunity. This article reviews the progress of the role of CD4+ T lymphocyte subsets in the development of GLM to explore potential therapeutic targets. Methods: Original articles from inception to October 2021 were systematically searched by two members on PubMed and China National Knowledge Infrastructure. Results: Current studies have confirmed the presence of disorders of several immune molecules in the serum and tissue microenvironment of GLM patients, including interleukin (IL) -2, IL-4, IL-6, and IL-10. This may be related to the dysregulation of Th1/Th2 and Th17/Treg balance. Conclusions: Altered expression and the malfunctioning of Th, Treg, and associated cytokines may contribute to GLM pathogenesis. Immune molecules and immune-related pathways may be potential targets and breakthroughs for future GLM treatment.